Knowledge, attitudes, and practices of gynaecologists and paediatricians regarding newborn hearing screening in Odisha - Behera, Dipika; Nandurkar, Aparna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Gynaecologists and paediatricians are crucial in detecting hearing loss at the first level of intervention. These healthcare workers are the ones who initially interact with infants and their parents. Therefore, they must understand the risk factors for newborn hearing loss and have a positive attitude toward early intervention. There were few studies conducted to evaluate the Knowledge Attitude and Practices (KAP) of New Born Hearing Screening (NBHS) among paediatricians and other physicians in Western countries and few in the Indian context. Thus, the current study aims to compare and examine the knowledge, attitudes, and practices of gynaecologists and paediatricians regarding newborn hearing screening in Odisha. Methods: A survey questionnaire containing 45 close-ended and 5 open-ended questions was developed. This questionnaire was validated by paediatricians, gynaecologists, and audiologists and then applied among 300 professionals in Odisha. Results: In all the sections it was found that paediatricians have greater knowledge than gynaecologists, however, both professionals have a positive attitude towards NBHS in Odisha. Mann-Whitney U test revealed significant differences in knowledge, attitudes, and practices among paediatricians and gynaecologists in Odisha. Conclusions: From this survey, it can be concluded that most of the paediatricians know more about paediatric hearing loss in comparison to gynaecologists, while both of them have positive attitude in implementing NBHS in Odisha. An awareness should be created among both the professionals about NBHS, effect of hearing loss and to whom they can refer for NBHS, which will benefit the newborns and their parents.